1994
DOI: 10.1182/blood.v83.6.1460.bloodjournal8361460
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the Ki-67-associated proliferative antigen in aggressive non-Hodgkin's lymphomas: a prospective Southwest Oncology Group trial

Abstract: The growth fraction of tumors from patients with non-Hodgkin's lymphomas (NHL) has been shown to correlate with survival in retrospective studies. The growth fraction can be evaluated using immunohistochemical techniques employing the Ki-67 monoclonal antibody (MoAb) that marks a nuclear protein present in cycling cells. The purpose of this study was to evaluate the clinical utility of the Ki-67 MoAb for predicting survival. Using a prospective trial design in a multi-institutional cooperative trials group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to assess the significance of Ki-67 expression in a sizable DLBCL patient cohort receiving a rituximab-containing regimen. High Ki-67 expression was associated with shorter OS and EFS, and higher relapse rates, consistent with previous data from the non-rituximab era on a prospective analysis of DLBCL (11), and mantle cell lymphoma treated with a rituximab-containing regimen (20). Our results indicated that the replication index was not related to the response of tumors to rituximab plus chemotherapy, in agreement with a previous report (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, the present study is the first to assess the significance of Ki-67 expression in a sizable DLBCL patient cohort receiving a rituximab-containing regimen. High Ki-67 expression was associated with shorter OS and EFS, and higher relapse rates, consistent with previous data from the non-rituximab era on a prospective analysis of DLBCL (11), and mantle cell lymphoma treated with a rituximab-containing regimen (20). Our results indicated that the replication index was not related to the response of tumors to rituximab plus chemotherapy, in agreement with a previous report (21).…”
Section: Discussionsupporting
confidence: 92%
“…However, strong p53 protein expression was correlated with p53 mutations, and prognostic significance for DLBCL patients treated with R-CHOP was maintained (29). The prognostic value of Ki-67 expression in DLBCL is still a controversial issue, although the prevailing concept is that high Ki-67 expression is associated with poor survival (9)(10)(11)(12)(14)(15)(16)(17)(18)(19). Variable results among study groups may result from diverse study populations, sample sizes, method of Ki-67 staining ⁄ assessment, chosen Ki-67 threshold, and heterogeneous therapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a correlation between the proliferative index (the proportion of Ki67-positive cells to tumor cells) and survival, as previously reported. 17 Four patients died; however, their proliferative index was less than 80%. A larger sample is needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 95%
“…However, other studies have shown that a high Ki-67 proliferation index is also a poor prognostic marker for DLBCL. 5,11 Overexpression of the P-glycoprotein product of mdr-1 gene is a well-characterized mechanism of drug resistance. Lee et al reported that strong MDR-1 immunoreactivity (Ͼ 50%) was an independent negative predictor of overall survival in canine lymphomas.…”
Section: Discussionmentioning
confidence: 99%